2005
DOI: 10.1002/ptr.1668
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind placebo-controlled trial of a standardized extract ofMatricariae recutita,Foeniculum vulgare andMelissa officinalis (ColiMil®) in the treatment of breastfed colicky infants

Abstract: The present study shows that colic in breastfed infant improves within 1 week of treatment with an extract based on Matricariae recutita, Foeniculum vulgare and Melissa officinalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 38 publications
(39 reference statements)
1
64
0
8
Order By: Relevance
“…14 -16 Lactobacillus reuteri, fennel seed oil, herbal tea, and an herbal preparation have all been shown to decrease daily crying in randomized controlled trials. [17][18][19][20] None of these trials reported adverse events, but the short-term and long-term safety is not known. Behavioral interventions, such as decreasing stimulation and providing parent support, have been taught to parents with mixed results on the amount of crying, [21][22][23][24][25] although an educational intervention has shown an increased knowledge about infant crying.…”
mentioning
confidence: 99%
“…14 -16 Lactobacillus reuteri, fennel seed oil, herbal tea, and an herbal preparation have all been shown to decrease daily crying in randomized controlled trials. [17][18][19][20] None of these trials reported adverse events, but the short-term and long-term safety is not known. Behavioral interventions, such as decreasing stimulation and providing parent support, have been taught to parents with mixed results on the amount of crying, [21][22][23][24][25] although an educational intervention has shown an increased knowledge about infant crying.…”
mentioning
confidence: 99%
“…В двойном слепом плацебо-контро-лируемом исследовании описан эффект от приема фен-хеля в виде уменьшения колик у новорожденного, нахо-дящегося на ГВ [56]. Анис описан как травяное средство, наиболее часто применяемое у плачущего младенца в арабских странах [57].…”
Section: в исследованияхunclassified
“…A study was carried out by Savino et al (2005) to test the effectiveness of a standardised extract of Matricaria recutita (chamomile), Foeniculum vulgare (fennel) and Melissa officinalis (lemon balm) (Colimil) in the treatment of breastfed colicky infants. Ninetythree breastfed colicky infants were enrolled in the study; the diagnosis of infantile colic was made according to Wessel's criteria.…”
Section: Herbal Extractsmentioning
confidence: 99%